Experimental and numerical study on tunnel linings strengthened with corrugated BFRP plates - Xinquan Chang; Xin Wang; Jingyang Zhou; Meili Lu; Xing Wei; Peng Liu; Zhishen Wu; Jason Ingham; Mohammad Noori (Tunnelling and Underground Space Technology, 2026)

Indigenous values in geothermal decision-making: A comparative analysis of governance constraints in Aotearoa New Zealand and Hawai‘i - Nona Taute; Te Kipa Kēpa Brian Morgan; Jason Ingham; Rosalind Archer; Tumanako Fa'aui (Environmental Impact Assessment Review, 2026)

An impact assessment and decision support tool for geothermal projects in Aotearoa - Nona Taute; Te Kipa Kēpa Brian Morgan; Jason Ingham; Rosalind Archer; Tumanako Fa'aui (Environmental Impact Assessment Review, 2026)

Analytical formulation describing the behaviour of URM walls seismically strengthened using timber strong-backs - Davide Cassol; Jason Ingham; Dmytro Dizhur; Ivan Giongo (Engineering Structures, 2025)

Bond-slip behavior of Aluminum Alloy (AA) bars for near-surface mounted (NSM) technique - Xu Chen; Guohua Xing; Da Luo; Yongjian Lu; Zhaoqun Chang; Enrique del Rey Castillo; Jason Ingham (Engineering Structures, 2025)

Seismic risk assessment for commercial masonry infill buildings within the Auckland region of New Zealand - Rijalul Fikri; Matt Gerstenberger; Jason Ingham (Bulletin of Earthquake Engineering, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Typological study and statistical assessment of parameters influencing earthquake vulnerability of commercial RCFMI buildings in New Zealand - Rijalul Fikri; Dmytro Dizhur; Jason Ingham (Bulletin of Earthquake Engineering, 2019)

Seismic performance of Reinforced Concrete Frame with Masonry Infill buildings in the 2010/2011 Canterbury, New Zealand earthquakes - Rijalul Fikri; Dmytro Dizhur; Kevin Walsh; Jason Ingham (Bulletin of Earthquake Engineering, 2019)

Experimental validation of seismic retrofit solutions for URM chimneys - Marta Giaretton; Jason M. Ingham; Dmytro Dizhur (Bulletin of Earthquake Engineering, 2018)